2023
DOI: 10.3390/life13020579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Morphological and Structural Skin Alterations on Diabetic Subjects by Biophysical and Imaging Techniques

Abstract: Diabetes causes increased production of advanced glycation end products (AGEs), which may lead to irreversible damage to collagen fibers, and early and more accentuated signs of skin aging. Thus, the objective of this study was to evaluate diabetic skin’s mechanical and morphological characteristics and compare these to healthy skin. Twenty-eight female participants aged between 39 and 55 years were enrolled: half had type 2 diabetes, and the others were healthy. Wrinkles, transepidermal water loss (TEWL), str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This is related to collagen-based AGE crosslinking, where these important fibers undergo structural and functional changes and eventually become bridled and dysfunctional [13,36]. This was linked to both a loss of elasticity and a greater presence of wrinkles [22]. In this study, elongation testing of the excised HTS specimen demonstrated that with skin deglycation and the reversal of AGE-induced crosslinking by use of FN3K, decreased scar rigidity can be obtained.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This is related to collagen-based AGE crosslinking, where these important fibers undergo structural and functional changes and eventually become bridled and dysfunctional [13,36]. This was linked to both a loss of elasticity and a greater presence of wrinkles [22]. In this study, elongation testing of the excised HTS specimen demonstrated that with skin deglycation and the reversal of AGE-induced crosslinking by use of FN3K, decreased scar rigidity can be obtained.…”
Section: Discussionmentioning
confidence: 68%
“…A recent publication by Moraes et al (2023) compared the skin parameters between a diabetic and healthy population using bio-functional measurements and reflectance confocal microscopy [22]. The authors showed that the skin quality was altered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spectral range 1000-1150 cm −1 , several bands in the spectra of the diabetic skin increase in intensity compared to the control sample, such as 1035 cm −1 , 1067 cm −1 , and 1100 cm −1 , which are associated with phenylalanine and proline [36,37,49]. According to Carcamo et al [49], proline has a broader band at 1100 cm −1 , attributed to N-C-H deformation, with increased intensity in the diabetic skin, suggesting the structural degradation of the collagen molecule [5,50,51], which we consider a pathological mechanism. L-arginine treatment does not reverse the intensities of these modes.…”
Section: Afm Analysismentioning
confidence: 99%